Potential of Leaf Extracts Sonneratia alba and Avicennia alba as a Biolarvacide of Aedes aegypti Mosquito - Muntaz Taufik Hidayat; Bintang Marhaeni; Siwi Pramatama Mars Wijayanti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
The continuous use of synthetic larvacides as an effort to control the vector mosquito population of Dengue Hemorrhagic Fever (DHF) can cause negative impacts on the environment and humans. Bioactive compounds from animals and plants can be used as an alternative to natural larvacides (biolarvacides). Mangrove species Sonneratia alba and Avicennia alba are known to have several bioactive types, so they are potential as biolarvacides. This study aimed to determine the potential of S. alba and A. alba leaf extracts as biolarvacides against Aedes aegypti mosquito larvae. This research was true experimental with a post-test-only group design. The larvicidal toxicity test of the leaf extracts of S. alba and A. alba against Ae. aegypti larvae to obtain the LC50 value was carried out by treating the extract concentrations at 500 ppm, 1,000 ppm, and 1,500 ppm. Synthetic larvicide (abate) was used as a positive control and Aquadest as a negative control. Data analysis was carried out descriptively and statistically (probit analysis). The results showed that the leaf extracts of S. alba and A. alba had potential as biolarvacides. Based on the LC50 value, the extracts of A. alba (LC50: 1,053 ppm) were more potent as biolarvacides than the extracts of S. alba (LC50: 14,112 ppm). Physical damage and behavioral changes in mosquito larvae movement indicated that the toxicity of A. alba leaf extract was acute while that of S. alba leaf extract was chronic.